Release of carbohydrates from sphingoglycolipid by osmium-catalyzed periodate oxidation followed by treatment with mild alkali - Sen-Itiroh Hakomori (Journal of Lipid Research, 1966)
The carbohydrate moiety of sphingoglycolipid, after preliminary acetylation, can be released by periodate oxidation catalyzed by a trace amount of osmium tetroxide, followed by alkaline treatment.Cerebroside, lactosyl ceramide, hematoside, globoside, and gangliosides were degraded to yield, respectively, galactose, lactose, sialyl lactose, a tetrasaccharide, and various oligosaccharides containing sialic acid. Oligosaccharides were separated by paper chromatography and paper electrophoresis. The procedure is useful for characterizing micromolar amounts of sphingoglycolipids.